PENGARUH SISTEM PENGENDALIAN INTERNAL TERHADAP PENCEGAHAN FRAUD PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021–2023 - Della Putri Hardiani; Caska, Caska; Fenny Trisnawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The prevalence of fraud cases across various industrial sectors in Indonesia highlights the critical importance of strengthening organizational protection mechanisms to maintain the integrity of financial reporting. This study was conducted to analyze the effect of the internal control system on fraud prevention in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2021–2023 period. This research utilizes a quantitative approach with a causality method. The research sample consists of 12 companies selected using a purposive sampling technique, resulting in a total of 36 observations over three years of study. Data were obtained through the documentation of officially published corporate annual reports. Data analysis was performed using linear regression with the Robust Standard Error (Huber-White) approach. The results of the study indicate that the internal control system has a positive and significant effect on fraud prevention. This is evidenced by a significance value of 0.000 < 0.05 and a regression coefficient of 0.989. These findings explain that a stronger internal control system leads to more effective fraud prevention efforts within the company. Accordingly, strengthening internal control elements is highly recommended as a primary strategy for management to minimize the risk of fraud.